2021
DOI: 10.1167/tvst.10.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Possible Correlation Between Retinal Neurovascular Biomarkers and Early Cognitive Impairment in Patients With Chronic Kidney Disease

Abstract: Purpose To investigate the association between retinal neurovascular biomarkers and early cognitive impairment among patients with chronic kidney disease (CKD). Methods Patients with CKD stage ≥3 were evaluated using the standardized Mini-Mental State Examination (MMSE). Patients were classified as having a low (<24), middle (24 to 27), and high (>27) MMSE level. Retinal nerve fiber layer thickness, ganglion cell complex (GCC) thickness, GCC global loss volume, and GCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Also, aMCI and non-amnestic MCI groups in [63] had a similar pRNFL-Avg thickness variations, and negligible differences. Furthermore, another study by [19] [63,72,81]. Specifically, the pRNFL-Avg thickness variations in [72] were insignificant when comparing MCI, dementia, and HCs in [72], and when correlating MCI, AD, DLB, VCID, FTD, and HCs.…”
Section: Optic Disc Related Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, aMCI and non-amnestic MCI groups in [63] had a similar pRNFL-Avg thickness variations, and negligible differences. Furthermore, another study by [19] [63,72,81]. Specifically, the pRNFL-Avg thickness variations in [72] were insignificant when comparing MCI, dementia, and HCs in [72], and when correlating MCI, AD, DLB, VCID, FTD, and HCs.…”
Section: Optic Disc Related Parametersmentioning
confidence: 95%
“…Some research works use the commercial software which accompanies the OCT/OCTA machine. For instance, both [19,35] extracted OCT and OCTA parameters automatically by a commercial RTVue XR software and Optovue AngioVue system (software ReVue XR). In addition, the AngioAnalytics™ software was used by [36] to compute VD and FD for retinal vasculature as well as the perimeter and Acircularity Index for FAZ.…”
Section: Extracting Oct/octa Parameters Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies using OCT have shown that a relatively thinner ganglion cell complex (GCC) or retinal nerve fiber layer (RNFL) was associated with cognitive impairment ( Cheung et al, 2015 ; Jones-Odeh and Hammond, 2015 ; Ko et al, 2018 ; Ito et al, 2020 ). However, only case-control and hospital-based studies using OCTA have investigated the vascular alternations in patients with AD using OCTA ( Zhang et al, 2020 ; Cheung et al, 2021 ; Peng et al, 2021 ). Findings from those studies were inconsistent and the effects of important sub-categorizations (i.e., sex, diabetes, hypertension) remain unknown ( Rifai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ongoing AHEAD clinical trial is launching an examination of plasma amyloid as a potential screening tool for this prevention trial. Chronic Kidney Disease (CKD) has well-established links with cognitive aging [25][26][27] . In our prior work, lower eGFR (estimated glomerular ltration rate) was associated with poorer neuropsychological functioning among community-dwelling Mexican Americans 27 .…”
Section: Introductionmentioning
confidence: 99%